EVALUASI DESKRIPTIF EMPAT PILAR KEPEMIMPINAN KEPALA SEKOLAH: UPAYA TRANSFORMASI MENUJU MANAJEMEN SEKOLAH YANG IDEAL - Gede Agung, Anak Agung; Chindytia; Ni Putu Priska Dewi Elicia Putri; Ayu Indah Pradnyadewi; Ni Made Wina Ayu Dwipayani (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study originated from the critical need to evaluate school principal leadership within the School-Based Management (SBM) framework. The investigation focused on the prevailing gap between structured administrative management and genuine staff engagement. The primary objective was to analyze the current leadership dynamics at SD 3 Buduk and identify strategic paths toward an ideal management model. A descriptive qualitative approach was employed, utilizing systematic observations across four fundamental leadership pillars. The findings reveal a striking contrast in leadership performance. While visionary and transparency indicators exhibit excellent standards, participatory decision-making remains at a mediocre level. This evidence suggests that an instructive leadership style persists despite high levels of information openness. Consequently, achieving ideal school management necessitates a shift toward collective collaboration. It is essential for the principal to foster deliberative dialogue, ensuring that systemic efficiency harmonizes with meaningful staff involvement to reach democratic educational excellence. Keywords: leadership, school-based management, visionary, participation, transparency.